Merck's manual of the materia medica (Merck & Co, 1899)
Containing names and chief synonyms, physical form and appearance, solubilities, percentage strengths and physiological effects, therapeutic uses, modes of administration and application, regular and maximum dosage, incompatibles, antidotes, precautionary requirements, etc., etc., of the chemicals and drugs usual in modern medical practice.